Translation for social justice: concepts, policies, and practices across modalities and contexts - Boeri, Julie (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2024)
The transnational nature of contemporary movements, media and networks in our globalised and interconnected societies has placed translation at the heart of counter-hegemonic discourses and endeavours. In this context, translation has become a powerful prism through which to think about and practise social justice. Although largely intellectualised in relation to Western liberal welfare states, social justice is also a performative and interpersonal prism of social change with roots historically spread across cultures, traditions and territories and with ramifications in contemporary forms of resistance. Thus, whereas social justice has traditionally been understood as the fair distribution of means and resources and the recognition of people’s rights across status in a given society, the increasing interconnection of struggles across the world has broadened social justice in ways that raise the stakes of translation. The leveraging and enactment of the multiple rights which social justice now encompasses is contingent on the organisation, the practice and the theorisation of translation in all its modalities (translation, interpreting, bilingual facilitation, fixing, subtitling, dubbing) and across communication contexts of resistance (social movements, media networks, cultural institutions). This special issue of the journal explores social justice by delving into specific areas and modalities of translation and interpreting practices. At the same time, it engages with macro-societal issues that affect these practices. These issues range from the power (and the limitations) of translation in circulating counter-hegemonic ideas and knowledge across borders in the publishing, media and cultural industries to the development of curricular, pedagogical and policy-making strategies in a higher education system that is both technologically disrupted and ableist-structured. The issues also include the public institutions’ exclusionary communication practices inherited from colonialisation, patriarchy, and ableism, and the subsequent expectations and actual practices of language professionals’ support to migrants and other vulnerable citizens in this context. The contributions gathered in this special issue contribute to expanding the boundaries of the constantly evolving field of translation while deepening our reflection on the ways in which education, research and practice may reproduce, contest and disrupt systemic injustices.